HALOGEN AND AR-AR AGE DETERMINATIONS OF INCLUSIONS WITHIN QUARTZ VEINS FROM PORPHYRY COPPER DEPOSITS USING COMPLEMENTARY NOBLE GAS EXTRACTION TECHNIQUES - Kendrick M.A.; Burgess R.; Pattrick R.A.D.; Turner G. (My University, 2001)
Extension of Ar-Ar methodology has been used to determine mineralisation ages from mica inclusions and to simultaneously evaluate the noble gas and halogen composition of inclusion fluids within irradiated quartz vein samples from five porphyry copper deposits. Samples have been collected from the potassic and propylitic zones of Bingham Canyon, Utah, and four Arizonan deposits; Silverbell, Globe-Miami, Pinto Valley and Ray. Data obtained using three noble gas extraction techniques (laser ablation, in vacuo crushing and stepped heating) are compared with each other. Laser ablation provides a means for the analysis of individual fluid inclusions but is limited by blank levels and detection limits. Stepped heating and in vacuo crushing are bulk extraction techniques that preferentially release gases from solid and fluid inclusion phases, respectively, and can be used in combination to obtain accurate and meaningful ages of mineralisation. Ages obtained for porphyry copper deposits are as follows: Bingham Canyon 37.1+/-0.5, Ray 65.3+/-1.5, Globe-Miami 61.7+/-3.4, Pinto Valley 63.2+/-8.0 and Silverbell 55.8+/-1.8. The age of mineralisation at Ray is of particular interest as it enables a reported discrepancy in K-Ar ages to be understood. Halogen data for the Bingham Canyon samples gives insight into the partitioning of the heavy halogens (Br and I) between solid and liquid phases.
Keywords: AR-AR; FLUID INCLUSIONS; QUARTZ; HALOGENS; PORPHYRY; NOBLE GASES